2001
DOI: 10.1053/eupc.2001.0186
|View full text |Cite
|
Sign up to set email alerts
|

QT dispersion in patients with mitral valve prolapse is related to the echocardiographic degree of the prolapse and mitral leaflet thickness

Abstract: Our results indicate that QT and JT dispersions are related to the echocardiographic degree of MVP and mitral leaflet thickness. The echocardiographic assessment of the severity of the prolapse may help to identify a subgroup of patients at increased risk of life-threatening arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…In studies involving adults, a close relation between ventricular arrhythymias and QT dispersion which is a criterion for regional differences in the ventricular repolarization period has been reported (7)(8)(9). In the study of Kulan et al (7) which involved 64 adult patients with primary MVP and 80 healthy individuals, it was shown that QT dispersion increased in the patient group and there was a correlation between the increase in QT dispersion and complex ventricular arrhythymias.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In studies involving adults, a close relation between ventricular arrhythymias and QT dispersion which is a criterion for regional differences in the ventricular repolarization period has been reported (7)(8)(9). In the study of Kulan et al (7) which involved 64 adult patients with primary MVP and 80 healthy individuals, it was shown that QT dispersion increased in the patient group and there was a correlation between the increase in QT dispersion and complex ventricular arrhythymias.…”
Section: Discussionmentioning
confidence: 93%
“…In studies involving adults, the frequency of ventricular arrhythmia in patients with primary MVP has been reported with a rate ranging between 49% and 89% depending on the patient group and MVP diagnostic criteria (21)(22)(23) Various causes have been proposed in formation of ventricular arrhythmias in primary MVP. These include stretching of the papillary muscles with ballooning prolapse of mitral leaflets (27), mechanical stimulation of the endocardium by thickened chordate (28), coronary emboly caused by accumulation of platalets and fibrin as a result of endocardial friction (29), autonomic dysfunction (30,31) and repolarization changes characterized by prolongation in QT interval and increase in QT dispersion (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zouridakis et al showed that patients with increased anterior mitral leaflet thickness were more likely to develop complex ventricular arrhythmias [24]. In addition, Nishimura et al reported that an increased mitral leaflet thickness was the only independent variable associated with sudden death in MVP patients [12].…”
Section: Discussionmentioning
confidence: 98%
“…Several reports showed alterations in ventricular repolarization, such as increased QT and QTc dispersions, in MVP patients [29,30]. In addition, the prolongation of QT dispersion was found to be associated with the degree of prolapse and thickness of the leaflets [31]. In a study of pediatric patients, QT dispersion values [55 ms were found to be more likely in cases of primary MVP than in cases of rheumatic MVP [24].…”
Section: Discussionmentioning
confidence: 95%